Technical analysis of renewable energy integration with battery energy storage systems on the Eskom grid - Gongxeka, Jacqueline (Department of Electrical Engineering, 2024)
The Eskom fleet of coal-fired power plants is ageing and will be retired within 30 years, if not sooner. As a clean alternative towards the decarbonization of the South African electrical industry, Eskom is progressively incorporating renewable energy sources into its infrastructure. However, the intermittent nature of renewable energy sources provides a challenge for supply security and system stability. There seems to be a need for Eskom to integrate large-scale energy storage into its grid to maintain energy security during the transition from fossil fuels to clean energy sources. Even though load shedding has been looming since 2008 and is getting worse as the fleet of power plants ages. Eskom is routinely curtailing wind energy in the early morning due to low demand, thereby wasting energy that could have been used during peak hours. In addition, Eskom's limited financial resources necessitate the delay of certain network strengthening projects. This dissertation examines the effects of Battery Energy Storage System (BESS) on the Eskom Distribution grid. This was accomplished by selecting two Eskom BESS sites, Skaapvlei (80 MW) which will be used for ancillary services (AS) and energy support (ES) and Hex (20 MW) which will be used for AS, ES and Load shaving (LS). Both networks were modelled using DigSilent Powerfactory and hourly load data from MV90 and the Eskom data tool. Eskom contractors' BESS models were used to simulate the future network, allowing for a comparison between the current network without BESS and the future network with BESS.